Determination of the Knowledge Levels of Nurses Regarding Central Venous Catheter Care - Hicran Türkkan; Tülay Kuzlu Ayyıldız; Münevver Sönmez (Galenos Yayinevi, 2022)
Introduction:It is important that pediatric nurses have sufficient knowledge in the prevention of central catheter-related blood circulation infections. This study was carried out to determine knowledge levels of the nurses, who were working in pediatric clinics, regarding central venous catheter care.Methods:The universe of the study was composed of 118 nurses, who were working in pediatric clinic of a public hospital (n=50) and a training hospital (n=68) between May-June 2019. No sample was selected; and 88 nurses, who were eligible for the sample and study criteria and approved to participate during the dates of data collection (May-June 2019) were included in the study. 75% of the universe was reached. Personal information form for the identification of demographic characteristics and working lives of the nurses and the form for the knowledge levels of the nurses regarding central venous catheter care were used to collect data.Results:At the end of statistical assessment, central venous catheter care mean score of nurses was found to be 8.35+2.36 (0-12). In addition, it was determined that no significant differences were found between central venous catheter scores of the nurses based on age, sex, marital status, working institution, working department, working year and their states of providing central venous catheter care (p>0.05). A significant difference was detected between nurses' states of having knowledge and education regarding central venous catheter and their central venous catheter scores (p<0.05).Conclusion:It was found that the knowledge points of the nurses for central venous catheter care were insufficient. It is recommended to increase in-service training in line with the protocol/procedure/ instructions regarding central venous catheter care.